2020
DOI: 10.1155/2020/9786182
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Fluid-Solid Coupling in Surrounding Rock for River Stope Mining

Abstract: Mining disturbance will induce further weakening of faults and rock bridges, improve rock mass permeability and, in serious cases, conduct surface rivers to cause disasters. A numerical calculation model of river-fault in the mining area is established. Based on the fluid-solid coupling theory of rock mass, the influence of mining disturbance on the development and evolution process of rock bridge rupture and river-fault-stope potential seepage channel is simulated and calculated. Research studies show that un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…In this section, we present cloud maps of pressure and velocity under different conditions, as shown in Figures 17-23. 20 Geofluids…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we present cloud maps of pressure and velocity under different conditions, as shown in Figures 17-23. 20 Geofluids…”
Section: Appendixmentioning
confidence: 99%
“…The behavior of mining of coal seams in the stope and the fault fracture zone interact with each other. The mining stress represented by the abutment pressure is the main inducement for the formation of the water-conducting fracture zone due to the floor failure and the "activation" of the fault water inrush [20,21]. At the same time, due to the influence of fracture, the stress distribution of surrounding rock in the stope and fracture area is more intensive, thus increasing the risk of floor instability [22].…”
Section: Introductionmentioning
confidence: 99%
“…Combining the acquired RMR values with the photo field locations in Table 1 yields a set of (x, y, z, RMR) data sets that will be used as sample points for block model assignment. Firstly, a solid model of the cube containing the estimated area was established to observe the rock mass distribution near the level of − 540 m more intuitively [51][52][53][54][55]. e z direction of the cube was − 560∼− 450 m, and the x and y directions were 529500∼532099 m and 3431599∼3433849 m, respectively; Secondly, the solid model is converted into a block model.…”
Section: D Visualization Of Engineering Rock Massmentioning
confidence: 99%
“…Yang et al [14] conducted three-dimensional fluid-solid coupled model tests to explore the evolution law of water inrush in karst caves which were induced by tunnel excavation and varying water pressure in the caves. Yuan et al [15] simulated the influence of mining disturbance in mines on the faults and rivers in the surrounding area based on the rock fluid-solid coupled theory. The results showed that mining activities can cause further damage to faults and rock bridges, causing increased rock permeability, which may allow mining filed to form a coalesced seepage channel spanning from a river to faults.…”
Section: Introductionmentioning
confidence: 99%